2021
DOI: 10.1155/2021/2897823
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Internet Commercial Judicial Based on Big Data Alliance and Mining Service Process Model

Abstract: At present, a series of economic structural changes created by the network economy have brought challenges to the entire economy and society. Traditional social commerce has also suffered severe tests under the background of network economy and global integration, and the rise and development of network commercial activities lack legal constraints. Based on the Big Data technology, in view of the characteristics of data mining services, this paper expands and changes the traditional model and proposes the Big … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
0
0
Order By: Relevance
“…The majority of Zhao's research on big data mining, feature selection, clustering, and granular computing, which can be used to process big data from social networks using text semantic processing, clustering, and other mining techniques (8) . Wan et al use particular scenarios to demonstrate the usefulness of the suggested approach.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of Zhao's research on big data mining, feature selection, clustering, and granular computing, which can be used to process big data from social networks using text semantic processing, clustering, and other mining techniques (8) . Wan et al use particular scenarios to demonstrate the usefulness of the suggested approach.…”
Section: Introductionmentioning
confidence: 99%